IMPLEMENTASI MULTI CRITERIA DECISION MAKING (MCDM) PADA AGROINDUSTRI: SUATU TELAAH LITERATUR - Rachman Jaya; Eka Fitria; Yusriana; Rizki Ardiansyah (Jurnal Teknologi Industri Pertanian, 2020)
Decision making process by decision maker in hard situation, limited time as well as uncertainty condition, is needed especially on agroindustry. The papers assessed an implementation of multi-criteria decision making (MCDM) method on agroindustrial decision making process. Several techniques in MCDM method has used by decision makers such as AHP, ANP, Vikor, TOPSIS, VIKOR, SAW, ELECTRE, PROMOTEE, MAUT, and MPE. The objectives of this research were to conduct literature review on an implementation of the techniques in MCDM on agroindustrial sectors and to determine a critically research topic to future works. The literature reviews were undertaken by 87 papers, technical report and handbooks which were related to the topic. Majority articles were downloaded through several scientific webs such as: DOAJ, Crossreef, Researchgate, Academia.edu, EBSCO, Google Scholar, Garuda-Ristek and Science Direct. The clusteritation based on logical framework, generic model and implementation to agroindustrial. At the end was discussed critical judgment on MCDM, particulary AHP and ANP. Keywords: agroindustrial, decision MCDM